Sistem Rekomendasi Pencarian Keahlian Mahasiswa Berdasarkan Curriculum Vittae Dengan Metode Simple Additive Weighting (SAW) - Fendi Aji Purnomo; Eko Harry Pratisto; Afif Zidan Nurrizqi (IJAI (Indonesian Journal of Applied Informatics), 2018)
The current technological developments, leading to the recruitment of skilled and ready-to-work Human Resources (HR) in the company to increase. Diploma III Program Informatics Engineering is one of the study program that produces skilled workers in the field of information technology (IT). There are several companies that request human resources graduate Diploma III Informatics Engineering, but the manager of the study program found it difficult to choose which graduates who have the skills required by the company. In this research has been made an application that can provide recommendations on the expertise inherent in the graduates using simple additive weighting method. The research method applied to design and make this system is by using Waterfall research method that is Software Requirements Gathering and Analysis, Design, Coding, and Testing. Decision Support System Curriculum Vitae is created using PHP-based programming framework YII 2 and MariaDB database. The application features consist of Curriculum Vitae data management function, Curriculum Vitae print, and Student recommendation search with user specified criteria weight. The results of manual and systematic simulation testing resulted in an appropriate ranking sequence in providing recommendations on the skills of the student.